Exploring Vocational Teachers’ Attitudes toward Academic Supervision: Does this Supervision Improve Their Pedagogical Competence? - Purba, Saut; ., Rosnelli; ., Kisno; ., Sherly; Purba, Desmalia; Panjaitan, Berkat (Journal of Posthumanism, 2025)
This article explores the impact of academic supervision on vocational teachers' attitudes and pedagogical competence. However, this study specifically investigates how it influences vocational teachers' attitudes toward pedagogical competence. The research involved semi-structured interviews with 68 vocational teachers, examining various aspects of academic supervision, including subject mastery, understanding of student characteristics, evaluation skills, and technology integration. Thematic content analysis revealed positive effects on pedagogical growth, industry integration, and curriculum enhancement. Nevertheless, challenges such as generalized feedback, limited ICT support, and a need for specialized approaches to academic supervision were identified. The study concludes by emphasizing the necessity for tailored academic supervision frameworks in vocational education to address these issues effectively. It acknowledges research limitations, including a small sample size, and calls for further exploration of solutions. Academic supervision remains a vital tool in shaping vocational education and nurturing a skilled workforce, and by addressing its limitations, it can continue to transform education.